Analisis Postur Kerja terhadap Gangguan Musculoskeletal pada Petani Padi di Kecamatan Cilamaya Wetan - Jilan Zainal Muqrobin; Dewi Indah Lestari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
The agricultural industry is among the sectors with a high incidence of work-related accidents and illnesses. Rice farmers are particularly vulnerable to musculoskeletal disorders (MSDs) due to repetitive and prolonged non-ergonomic working postures. This purpose of this  to analyze the risk levels associated with the working postures of rice farmers. Based on questionnaire data collected from 84 rice farmer respondents, it was found that these farmers face a high risk of experiencing musculoskeletal issues due to poor working postures. Data were gathered through observations of working postures and the Nordic Body Map Discomfort questionnaire. The findings indicate that the respondent characteristics are predominantly male (70.2%), with an average age of 39.32 years and an average work duration of 18.52 years. The prevalence of musculoskeletal complaints reached 77.4%. REBA analysis revealed that 58.3% of respondents fell into the very high-risk category, 14.3% into the high-risk category, and 27.4% into the medium-risk category. Statistical tests demonstrated a significant relationship between the level of work risk and musculoskeletal complaints (p-value = 0.001), with a weak correlation strength (r=0.214). Results indicate that the working posture of rice farmers poses a high risk of causing musculoskeletal disorders, necessitating comprehensive ergonomic interventions. Recommendations from this research include adequate rest time management, the use of assistive tools, ergonomic training, and the development of further research methods incorporating more comprehensive variables.